Exact Calculation of Social Distancing at Ongoing COVID-19 Pandemic by Using Simple Kinematics of Aerosols - Nieto-Chaupis, Huber (2022)
In the ongoing Covid-19 panemic the social distance is needed to guarantee healthy oral Communications even with the wearing of a mask. In this paper the so-called social distancing is calculated with the usage of simple kinematics and other physics-based concepts. According to the calculations of this study the distance depends on the square root of a logarithm and the initial number of expelled aerosols per unit of volume. Computational simulations were carried out. The result havd shown that the environment that supports the lifetime of aerosol is a relevant variable that suggests that thermodynamics needs to be applied to formulate a precise theory of infection based at aerosols in order to estimate an universal social distancing policy.